Attempt to Create A New Model to Predict The Financial Failure of Business Companies - Chaaib , Pr. Chennouf; Souhiela , Dr. Hanoune (International Journal of Accounting and Economics Studies, 2025)
This research paper has two main objectives. The primary objective was to gain a deeper understanding of the ‎relationship between financial ratios and financial failure, to develop an early warning system ‎for detecting financial distress. The second purpose is to develop a new model, CHENNOUF’s Model, for ‎predicting financial failure.‎ This study examined 18 companies between 2012 and 2024 to test this model. Data were collected ‎over 12 years, and we studied and analyzed the relationship between 75 financial ratios and financial failure in order to build a model to predict the failure of ‎companies before it occurred.‎ This study is based on an analytical method and inferential statistical analysis of the independent variables that ‎define the ratios used in calculating the predicted failure or financial success. We have been working on this ‎model for eight years; we have worked on developing a new model to predict financial failure. We faced ‎several difficulties; however, we incorporated artificial intelligence tools at some points in this research, such as ‎relative weights and correlations. In addition, we used Excel to calculate the bankruptcy index.‎ After examining the problem of this study, we obtained a number of results. Despite the generality and some limitations in the new ‎model, it must be developed by future research.‎ The present paper represents, in our view, one of the most important attempts to address and explain the ‎relationship between financial failure and financial ratios. After examining and analyzing the relationship ‎between financial ratios and financial failure, we obtain the following new model:‎ FS=0.146C+0.103H+0.187E+0.192N1+0.013N2+0.125O+0.138U+0.10F.